2015
DOI: 10.4292/wjgpt.v6.i2.17
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of clopidogrel-proton pump inhibitors interaction

Abstract: Clopidogrel is a widely used antiplatelet agent for the secondary prevention of cardiovascular events in patients with stable coronary heart disease, acute coronary syndromes and ischemic stroke. Even though clopidogrel is safer than aspirin in terms of risk for gastrointestinal (GI) bleeding, the elderly, and patients with a history of prior GI bleeding, with Helicobacter pylori infection or those who are also treated with aspirin, anticoagulants, corticosteroids or nonsteroidal antiinflammatory drugs are at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 42 publications
1
19
0
3
Order By: Relevance
“…Clopidogrel is a first‐line anti‐platelet prodrug indicated for the secondary prevention of atherothrombotic cardiovascular disease . Pharmacokinetic studies have postulated an interaction between PPIs and clopidogrel, arising from metabolism by the same hepatic isoenzyme (CYP2C19) . Inhibition of CYP2C19 by PPIs may reduce the bioavailability of the active metabolites of clopidogrel, and attenuate clopidogrel's cardiovascular benefits .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clopidogrel is a first‐line anti‐platelet prodrug indicated for the secondary prevention of atherothrombotic cardiovascular disease . Pharmacokinetic studies have postulated an interaction between PPIs and clopidogrel, arising from metabolism by the same hepatic isoenzyme (CYP2C19) . Inhibition of CYP2C19 by PPIs may reduce the bioavailability of the active metabolites of clopidogrel, and attenuate clopidogrel's cardiovascular benefits .…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Inhibition of CYP2C19 by PPIs may reduce the bioavailability of the active metabolites of clopidogrel, and attenuate clopidogrel's cardiovascular benefits. [16][17][18] As a result, the United States Food and Drug Administration (FDA) has warned against using clopidogrel in combination with the PPIs omeprazole and esomeprazole. 19 Observational studies and randomised controlled trials have yielded conflicting results as to whether the proposed pharmacokinetic interaction between PPIs and clopidogrel manifests as an increased clinical risk of adverse cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, several researchers have discussed whether PPIs may attenuate the cardiovascular protection of clopidogrel for patients with acute coronary syndrome. [23][24][25][26] Additionally, the single use of PPIs also has potentially adverse clinical outcomes in high-risk cardiovascular populations.…”
Section: Ppis and Myocardial Infarctionmentioning
confidence: 99%
“…18,19 A randomised trial found no evidence of an increased risk of cardiovascular events in patients taking PPIs and thienopyridines such as clopidogrel. 10,20 There was also no evidence that separating the doses of the two drugs changed cardiac risk. 21 If there are major concerns about the interaction, a PPI with less cytochrome P450 (CYP) metabolism such as rabeprazole may be used.…”
Section: Adverse Effectsmentioning
confidence: 99%